14 Medications that affect the lower oesophageal sphincter and risk of oesophageal cancer: a cohort study of 465, 768 uk biobank participants. (5th April 2017) - Spence, A; Kunzmann, A; McMenamin, U; Coleman, H; Johnston, B; Murray, L; Cardwell, C
Abstract : Background: Medications that relax the lower oesophageal sphincter may promote acid reflux, a known contributor to oesophageal adenocarcinoma development. Aim: We investigated the association between lower oesophageal sphincter relaxing medications and oesophageal cancer (OC) risk. Method: A retrospective cohort study of participants within the UK Biobank from 2006 and 2014 was performed. Age-dependent Cox-regression analysis was used to calculate adjusted HR and 95% CI for OC risk in individuals prescribed benzodiazepines, calcium channel blockers, nitrates, respiratory sympathomimetics and xanthines. Results: Of 4 75 768 study participants, 409 were diagnosed with OC during 8 years of follow-up. There was a significant direct association with OC in participants using respiratory sympathomimetics (HR 1.71, 95% CI 1.20–2.42), with similar increased risk of oesophageal adenocarcinoma with use of these respiratory medications (HR 1.68, 95% CI 1.10–2.54) and xanthines (HR 4.82, 95% CI 1.16–20.10). Participants taking respiratory sympathomimetics or any lower oesophageal sphincter relaxing medication were also at greater risk of oesophageal squamous cell cancer (HR 2.51, 95% CI 1.29–4.87 and HR 2.03, 95% CI 1.01–4.09, respectively). There was no significant association between OC and the other medications investigated. Conclusions: Respiratory sympathomimetics were associated with greater risk of OC overall, and both adenocarcinoma and squamous cell carcinoma subtypes. Individuals using lower oesophageal sphincter relaxing medications are at increased risk of squamous cell carcinoma, and as this tumour is not associated with excessive acid reflux, an alternative pathway to this cancer with these medications may exist.